2001
DOI: 10.1111/j.1151-2916.2001.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field Effects on Sintering and Reaction to Form Aluminum Titanate from Binary Alumina–Titania Sol–Gel Powders

Abstract: The field-activated sintering technique (FAST) was applied to simultaneously sinter and react sol-gel amorphous powders to form Al 2 TiO 5 . Densities close to theoretical and conversion to Al 2 TiO 5 (to 92.5%) have been achieved using FAST at 1050°-1200°C for 10 min. Conventional sintering of the same powders at 1300°C for 2 h resulted in 88.9% Al 2 TiO 5 and ϳ75% of theoretical density. The enhanced sintering and compound formation using FAST have been explained by the synergistic effects of precursor react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…We further note that this reaction occurs at a temperature that is below the normal phase diagram temperature for the formation of aluminum-titanate. A similar effect has been observed when powders prepared by sol-gel are sintered by spark-plasma-sintering [32,33].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We further note that this reaction occurs at a temperature that is below the normal phase diagram temperature for the formation of aluminum-titanate. A similar effect has been observed when powders prepared by sol-gel are sintered by spark-plasma-sintering [32,33].…”
Section: Discussionsupporting
confidence: 71%
“…Our experiments are different: we show that alumina and titania can react and merge, forming the titanate phase under electrical fields at temperature where they are normally expected to remain as individual phases. A similar effect has been seen in SPS processing with powders prepared by the sol-gel process [32,33], where aluminum titanate has been shown to form at temperatures below the nomial phase transformation temperature of 1280 o C.…”
Section: Introductionsupporting
confidence: 62%
“…Thus, the loss of the mechanical strength of these specimens was related to the growth and propagation of cracks. This behavior has already been reported for highly microcracked TiO 2 -Al 2 O 3 samples [56,57]. It is well established that aluminum titanate exhibits an anisotropic thermal expansion along the three primary axes of the crystal lattice, which leads to the formation of microcracks [58,59].…”
Section: Characterizationmentioning
confidence: 58%
“…The technique uses a pulsed electric field application together with high‐heating rates and pressure to sinter a large variety of powder materials, both conductive and nonconductive 1–4 . It was shown that the electric field has an activating effect on mechanisms that dominate each stage of the process (surface activation by the pulsed current, acceleration of diffusion kinetics), resulting in enhanced densification and an increase in the rate of sintering neck growth 5–7 . This is probably due to phenomena such as localized overheating at particle contacts and the removal of impurities by electrical discharges.…”
Section: Introductionmentioning
confidence: 99%